The Degree of Geographic Teacher of Using the Modern Educational Techniques in Ajloun Governorate and their Attitudes toward technique from their Perspective - BaniAta, Majedah Ali Mahmoud (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of geographic teacher of using the modern educational techniques in Ajloun governorate and their attitudes toward technique from their perspective, the study used the descriptive analysis approach, two questionnaires were development first one to determine the level of geographic teacher of using the modern educational techniques, the second to determine attitudes toward technique, the sample of study consisted from (70) female and male teacher. However, the finding of study showed that the degree of geographic teacher of using the modern educational techniques in Ajloun governorate was moderated with average (3.53 out of 5), and their attitudes toward technique from their perspective was high with average (3.97 out of 5). The finding also showed there weren’t any significant difference in the degree of using the modern educational techniques in Ajloun governorate and their attitudes toward technique from their perspective refers to variable of teacher’s sex. Furthermore, there were significant differences at (α ≤ 0.05) according to teacher qualification for higher education.